Parallel information processing in motor systems: intracerebral recordings of readiness potential and CNV in human subjects - Rektor, I (Neural plasticity, 2000)
We performed intracerebral recordings of Readiness Potential (RP) and Contingent Negative Variation (CNV) with simple repetitive distal limb movement in candidates for epilepsy surgery. In 26 patients (in Paris), depth electrodes were located in various cortical structures; in eight patients (in Brno), in the basal ganglia and the cortex. RPs were displayed in the contralateral primary motor cortex, contralateral somato-sensory cortex, and bilaterally in the SMA and the caudal part of the anterior cingulate cortices. CNVs were recorded in the same cortical regions as the RP, as well as in the ipsilateral primary motor cortex, and bilaterally in the premotor fronto-lateral, parietal superior, and middle temporal regions. In the basal ganglia, the RP was recorded in the putamen in six of seven patients, and in the head of the caudate nucleus and the pallidum in the only patient with electrodes in these recording sites. We suggest that our results are consistent with a long-lasting, simultaneous activation of cortical and subcortical structures, before and during self-paced and stimulus-triggered movements. The particular regions that are simultaneously active may be determined by the task context.
Keywords: Movement; Contingent Negative Variation; kontingentní negativní variace; pohyb; Electrophysiology; somatosenzorické korové centrum; lidé; Motor Cortex; Somatosensory Cortex; mozek; Epilepsies, Partial; Electromyography; Brain; motorické korové centrum; elektrofyziologie; elektroencefalografie; epilepsie parciální; elektromyografie; Electroencephalography; Humans